Dirac-Nijenhuis structures - Clemente-Gallardo, J. (2003)
We introduce the concept of Dirac-Nijenhuis structures as those manifolds carrying a Dirac structure and admitting a deformation by Nijenhuis operators which is compatible with it. This concept generalizes the notion of Poisson-Nijenhuis structure and can be adapted to include the Jacobi-Nijenhuis case.